Lithium-sulfur battery electrolyte, preparation method and application thereof, and lithium-sulfur battery
By adding bismuth-containing organic additives to the lithium sulfur battery electrolyte, using its complexing effect with polysulfide and alloying reaction on the surface of the lithium negative electrode, the problems of poor cycle stability and low rate performance of lithium sulfur batteries are solved, and the battery performance is significantly improved.
Patent Information
- Application Number
- CN202311175797.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-12
- Publication Date
- 2025-03-14
AI Technical Summary
Due to the poor conductivity of elemental sulfur, the solubleness of long-chain polysulfides and the toxicity of lithium negative electrodes, lithium sulfur batteries have poor cycle stability, low discharge specific capacity and poor rate performance, which limits their market-oriented applications.
Bismuth-containing organic additives are used in the lithium sulfur battery electrolyte, through its complexation with polysulfides and alloying reaction on the surface of the lithium negative electrode, a bismuth-sulfur bond and bismuth-lithium alloy phase structure is formed to prevent the loss of polysulfides and improve the discharge specific capacity and cycle stability of the battery.
It significantly improves the rate performance, cycle performance and cycle life of lithium sulfur batteries, reduces the energy on the lithium deposition surface, slows down the nucleation and growth of lithium dendrites, and improves the safety of the battery.
Smart Images

Figure CN119627212A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a lithium-sulfur battery electrolyte and a preparation method and application thereof, and a lithium-sulfur battery, belonging to the technical field of lithium-sulfur batteries. Background Art
[0002] Elemental sulfur has the advantages of high theoretical specific capacity (1675mAh / g), high theoretical specific energy (2600Wh / kg), abundant reserves, low price and environmental friendliness, making it one of the most promising electrode materials in the next generation of high specific energy (single specific energy ≥ 350Wh / kg) battery systems. Especially in application areas such as drones and electric vehicles that require higher battery energy density (single specific energy ≥ 500Wh / kg), lithium-sulfur batteries will have great market competitiveness. The lithium-sulfur battery with elemental sulfur as the positive electrode active material will undergo the conversion of "elemental sulfur--> long-chain polysulfide (Li2S8 to Li2S4)--> short-chain sulfide (Li2S2 and Li2S)" during the discharge reaction, and the conversion direction is the opposite during the charging process. However, elemental sulfur itself has poor conductivity (at room temperature, i.e., 25°C, the conductivity is only 5×10 -30 S / cm), and the long-chain polysulfides formed with lithium ions during the charge and discharge process are easily soluble in the organic electrolyte and shuttle between the two sides of the diaphragm, resulting in a high self-discharge rate, and easy deposition on the lithium negative electrode, leading to the poisoning of the lithium negative electrode and the loss of active sulfur materials. As a result, lithium-sulfur batteries constructed with elemental sulfur as the positive electrode have the disadvantages of poor cycle stability, low discharge specific capacity, and poor rate performance, which restricts the further marketization of lithium-sulfur batteries.
[0003] At present, many researchers have used various methods to improve the electrochemical properties of sulfur electrodes, such as using carbon materials and / or oxide materials to compound with sulfur electrodes to improve the conductivity and cycle performance of the resulting sulfur cathode composite materials. Among them, carbon materials include activated carbon, carbon tubes, carbon fibers, graphene, graphene oxide, etc. with various pore structures; oxide materials include cobalt oxide, titanium oxide, silicon oxide, manganese oxide, etc. The application of these carbon materials and / or oxide materials has improved certain aspects of the performance of sulfur cathode composite materials, such as specific capacity, rate performance, and cycle performance. However, the preparation process of the material is relatively complex and the cost is high, making it difficult to achieve industrial production and application.
[0004] In addition, the current research in the field of electrolytes has also achieved good results. For example, the coulombic efficiency and cycle performance of the battery can be improved by adding suitable additives to the electrolyte. However, these additives often cannot take into account both the rate performance and the cycle performance while improving the coulombic efficiency. At present, the additive of lithium-sulfur battery electrolyte is mainly LiNO3, which has a significant effect on improving the coulombic efficiency of the battery, but has no obvious effect on improving the rate performance and cycle life of the battery. During the charging and discharging process of lithium-sulfur batteries, LiNO3 can form an SEI film on the surface of the lithium negative electrode, which plays a role in protecting the lithium negative electrode, but cannot prevent the dissolution of polysulfides and the chemical reaction between polysulfides and the lithium negative electrode. Therefore, how to optimize the electrolyte by selecting suitable bifunctional additives in the preparation process of lithium-sulfur batteries, so as to prepare lithium-sulfur batteries with low cost, simple process and excellent performance, will be of great significance to the industrial application development of lithium-sulfur batteries.
[0005] In summary, providing a new type of lithium-sulfur battery electrolyte and its preparation method and application and lithium-sulfur battery has become a technical problem that needs to be urgently solved in this field. Summary of the invention
[0006] In order to solve the above-mentioned shortcomings and deficiencies, an object of the present invention is to provide a lithium-sulfur battery electrolyte.
[0007] Another object of the present invention is to provide a method for preparing the above-mentioned lithium-sulfur battery electrolyte.
[0008] Another object of the present invention is to provide the use of the above-mentioned lithium-sulfur battery electrolyte as an electrolyte used in lithium-sulfur batteries.
[0009] Another object of the present invention is to provide a lithium-sulfur battery, the electrolyte used in the lithium-sulfur battery electrolyte is the above-mentioned.
[0010] In order to achieve the above objectives, on the one hand, the present invention provides a lithium-sulfur battery electrolyte, wherein, based on the total volume of the lithium-sulfur battery electrolyte, it comprises a lithium salt with a molar concentration of 0.2-2 mol / L, a bismuth-containing organic additive with a molar concentration of 0.005-0.2 mol / L, and a balance of an organic solvent.
[0011] As a specific embodiment of the lithium-sulfur battery electrolyte described above in the present invention, the bismuth-containing organic additive includes triphenylbismuth (C 18 H 15 Bi), bismuth trifluoromethanesulfonate (Bi(CF3SO3)3), tri-p-tolyl bismuth (C 21 H 21 Bi) and tri-o-tolylbismuth (C 21 H 21 Bi) etc.
[0012] When two or more bismuth-containing organic additives are used in combination in the present invention, there is no specific requirement for the usage ratio between the bismuth-containing organic additives, and they can be reasonably adjusted according to needs, as long as the molar concentration of the bismuth-containing organic additives in the lithium-sulfur battery electrolyte is ensured to be 0.005-0.2 mol / L.
[0013] As a specific embodiment of the lithium-sulfur battery electrolyte described above in the present invention, the lithium salt includes at least one of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium bis(fluorosulfonyl)imide (LiFSI), lithium trifluoromethanesulfonate (LiSO3CF3), lithium perchlorate (LiClO4), lithium hexafluorophosphate (LiPF6) and lithium nitrate.
[0014] When two or more lithium salts are used in combination in the present invention, there is no specific requirement for the usage ratio between the lithium salts, and it can be reasonably adjusted according to needs, as long as the molar concentration of the lithium salt in the lithium-sulfur battery electrolyte is ensured to be 0.2-2 mol / L.
[0015] As a specific embodiment of the lithium-sulfur battery electrolyte described above in the present invention, the organic solvent includes at least two of 1,3-dioxolane (DOL), ethylene glycol dimethyl ether (DME), ethylene carbonate (EC), fluorinated ethylene carbonate (FEC), dimethyl carbonate (DMC), diethyl carbonate (DEC), dimethyl trisulfide (DMTS) and dimethyl disulfide (DMDS).
[0016] When two or more organic solvents are used in combination in the present invention, there is no specific requirement for the usage ratio between the organic solvents, and it can be reasonably adjusted according to needs, as long as the total usage of the organic solvents meets the requirements of the lithium-sulfur battery electrolyte.
[0017] In the lithium-sulfur battery electrolyte provided by the present invention, the bismuth-containing functional group in the bismuth-containing organic additive is easy to produce complexation with polysulfides in the electrolyte (polysulfides formed by elemental sulfur and lithium ions during charging and discharging, and which are easily soluble in the organic electrolyte), thereby promoting the redox reaction between long-chain polysulfides and short-chain sulfides, and the formed bismuth-sulfur bonds can effectively prevent the loss of polysulfides, thereby improving the discharge specific capacity and capacity retention rate of the lithium-sulfur battery; the bismuth-containing organic additive can also be used as a catalyst to accelerate the conversion efficiency of polysulfides and improve the discharge rate of the battery; in addition, during the charging process, the bismuth-containing organic additive can also be decomposed in situ, and the bismuth-containing functional group is easy to alloy with the lithium metal negative electrode on the surface of the lithium metal negative electrode to form a bismuth-lithium alloy phase structure, thereby forming a uniform lithium deposition site, thereby reducing the lithium deposition surface energy, effectively slowing down the nucleation and growth probability of lithium dendrites, improving the capacity retention rate and cycle stability of the battery, and improving the cycle life and safety of the lithium-sulfur battery.
[0018] On the other hand, the present invention also provides a method for preparing the above-mentioned lithium-sulfur battery electrolyte, wherein the preparation method comprises:
[0019] Step 1: In a glove box filled with inert gas, mix the required organic solvents according to the proportion, and mix them evenly to obtain a basic solution;
[0020] Step 2: Add the dried lithium salt to the basic solution and mix well to obtain a basic electrolyte;
[0021] Step 3: Add the bismuth-containing organic additive to the basic electrolyte and mix well to obtain a lithium-sulfur battery electrolyte.
[0022] As a specific embodiment of the preparation method described above in the present invention, in step 1, the inert gas includes argon gas or the like.
[0023] As a specific embodiment of the preparation method described above of the present invention, in step 1, the water and oxygen contents in the glove box are both less than 0.1 ppm.
[0024] As a specific embodiment of the preparation method described above, in step 2, the drying is performed at 100-150° C. for 12-24 hours. In some embodiments of the present invention, the drying can be performed in a vacuum drying oven.
[0025] In another aspect, the present invention also provides use of the above-mentioned lithium-sulfur battery electrolyte as an electrolyte for lithium-sulfur batteries.
[0026] In another aspect, the present invention further provides a lithium-sulfur battery, wherein the electrolyte used in the lithium-sulfur battery is the lithium-sulfur battery electrolyte described above.
[0027] Compared with the prior art, the lithium-sulfur battery electrolyte provided by the present invention has the following advantages:
[0028] (1) The preparation method is simple. By using existing commercial reagents and simply preparing them in a certain proportion, the desired lithium-sulfur battery electrolyte that can significantly improve the rate performance and cycle life of the lithium-sulfur battery can be obtained;
[0029] (2) The effect is remarkable. The bismuth-containing functional groups in the bismuth-containing organic additives react with the polysulfides in the electrolyte to form a complex and alloy on the surface of the lithium negative electrode, which effectively improves the rate, cycle performance and cycle life of the battery.
[0030] (3) The lithium-sulfur battery electrolyte is easy to operate when used in lithium-sulfur batteries, and the lithium-sulfur battery electrolyte is relatively low in cost and easy to industrialize, which has played a certain role in promoting the industrial application of lithium-sulfur batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0032] Figure 1 Schematic diagram of comparison of cycle curves of lithium-sulfur batteries assembled using the lithium-sulfur battery electrolyte provided in Example 1 and Comparative Example 1 as the electrolyte. DETAILED DESCRIPTION
[0033] It should be noted that the term "comprises" and any variations thereof in the specification and claims of the present invention and the above-mentioned drawings are intended to cover non-exclusive inclusions. For example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices.
[0034] "Scope" disclosed in the present invention is given in the form of lower limit and upper limit. It can be one or more lower limits, and one or more upper limits respectively. A given range is defined by selecting a lower limit and an upper limit. The selected lower limit and upper limit define the boundaries of a particular range. All ranges defined in this way are combinable, i.e. any lower limit can be combined with any upper limit to form a range. For example, for a specific parameter, a range of 60-120 and 80-110 is listed, and it is understood that a range of 60-110 and 80-120 is also expected. In addition, if the minimum range values listed are 1 and 2, and the maximum range values listed are 3, 4 and 5, then the following ranges can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5.
[0035] In the present invention, unless otherwise specified, the numerical range "ab" represents an abbreviation of any real number combination between a and b, where a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" have been listed in the present invention, and "0-5" is just an abbreviation of these numerical combinations.
[0036] In the present invention, unless otherwise specified, all embodiments and preferred embodiments mentioned in the present invention can be combined with each other to form a new technical solution.
[0037] In the present invention, unless otherwise specified, all technical features and preferred features mentioned in the present invention can be combined with each other to form a new technical solution.
[0038] In the present invention, if not specifically stated, the term "two" used in this specification means "at least two".
[0039] In the present invention, unless otherwise specified, all steps mentioned herein may be performed sequentially or randomly, but are preferably performed sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0040] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with the attached table, drawings and examples. The following described embodiments are some embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be regarded as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention. If the specific conditions are not specified in the embodiments, they are carried out according to the normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0041] Lithium-sulfur battery electrolyte embodiments and comparative examples
[0042] Example 1
[0043] This embodiment provides a lithium-sulfur battery electrolyte, which includes a lithium salt, a bismuth-containing organic additive, and an organic solvent;
[0044] The lithium salt is LiTFSI and LiNO3, and the molar concentrations of LiTFSI and LiNO3 are 1 mol / L and 0.1 mol / L respectively, based on the total volume of the lithium-sulfur battery electrolyte;
[0045] The bismuth-containing organic additive is C 18 H 15 Bi, based on the total volume of the lithium-sulfur battery electrolyte, has a molar concentration of 0.01 mol / L;
[0046] The organic solvents are DOL and DME, and the volume ratio of the two is 1:1;
[0047] Wherein, the preparation method of the lithium-sulfur battery electrolyte comprises:
[0048] Step 1: In a glove box filled with argon, DOL and DME were mixed in a volume ratio of 1:1 to prepare 50 mL of a basic solution, wherein the water content in the glove box was less than 0.1 ppm and the oxygen content was less than 0.1 ppm;
[0049] Step 2: Place 14.35 g of LiTFSI and 0.345 g of LiNO3 in a vacuum drying oven and dry at 100 ° C for 24 h, then slowly add the dried LiTFSI and LiNO3 to 50 mL of the basic solution and mix well to obtain a basic electrolyte;
[0050] Step 3: Add 0.22 g of C 18 H 15 Bi is slowly added into the basic electrolyte and mixed evenly to obtain the required C 18 H 15 Lithium-sulfur battery electrolyte with Bi molar concentration of 0.01 mol / L.
[0051] Example 2
[0052] This embodiment provides a lithium-sulfur battery electrolyte, which differs from Embodiment 1 only in that:
[0053] Based on the total volume of the lithium-sulfur battery electrolyte, C 18 H 15 The molar concentration of Bi is 0.05 mol / L.
[0054] Example 3
[0055] This embodiment provides a lithium-sulfur battery electrolyte, which differs from Embodiment 1 only in that:
[0056] Based on the total volume of the lithium-sulfur battery electrolyte, C 18 H 15 The molar concentration of Bi is 0.1 mol / L.
[0057] Example 4
[0058] This embodiment provides a lithium-sulfur battery electrolyte, which differs from Embodiment 1 only in that:
[0059] The bismuth-containing organic additive is C 21 H 21 The molar concentration of Bi (tri-p-tolylbismuth) is 0.05 mol / L based on the total volume of the lithium-sulfur battery electrolyte.
[0060] Example 5
[0061] This embodiment provides a lithium-sulfur battery electrolyte, which differs from Embodiment 1 only in that:
[0062] The bismuth-containing organic additive is C 21 H 21 Bi (tri-p-tolyl bismuth), based on the total volume of the lithium-sulfur battery electrolyte, has a molar concentration of 0.1 mol / L.
[0063] Example 6
[0064] This embodiment provides a lithium-sulfur battery electrolyte, which differs from Embodiment 1 only in that:
[0065] The bismuth-containing organic additive is C 21 H 21 The molar concentration of Bi (tri-p-tolylbismuth) is 0.2 mol / L based on the total volume of the lithium-sulfur battery electrolyte.
[0066] Comparative Example 1
[0067] This comparative example provides a lithium-sulfur battery electrolyte, which differs from Example 1 only in that:
[0068] Contains no bismuth-containing organic additives.
[0069] Example 7
[0070] This embodiment provides a lithium-sulfur battery electrolyte, which includes a lithium salt, a bismuth-containing organic additive, and an organic solvent;
[0071] The lithium salts are LiTFSI and LiFSI, and the molar concentrations of LiTFSI and LiFSI are 0.5 mol / L and 0.5 mol / L, respectively, based on the total volume of the lithium-sulfur battery electrolyte;
[0072] The bismuth-containing organic additive is C 18 H 15 Bi, based on the total volume of the lithium-sulfur battery electrolyte, has a molar concentration of 0.05 mol / L;
[0073] The organic solvents are DOL, DME and DMDS, and the volume ratio of the three is 1:1:1;
[0074] Wherein, the preparation method of the lithium-sulfur battery electrolyte comprises:
[0075] Step 1: In a glove box filled with argon, DOL, DME and DMDS were mixed in a volume ratio of 1:1:1 to prepare 50 mL of a basic solution, wherein the water content in the glove box was less than 0.1 ppm and the oxygen content was less than 0.1 ppm;
[0076] Step 2: Put 7.18 g of LiTFSI and 4.67 g of LiFSI into a vacuum drying oven and dry them at 150 ° C for 12 h, then slowly add the dried LiTFSI and LiFSI into 50 mL of the basic solution and mix well to obtain the basic electrolyte;
[0077] Step 3: Add 1.1 g of C 18 H 15 Bi is slowly added into the basic electrolyte and mixed evenly to obtain the desired lithium-sulfur battery electrolyte.
[0078] Example 8
[0079] This embodiment provides a lithium-sulfur battery electrolyte, which differs from Embodiment 7 only in that:
[0080] Based on the total volume of the lithium-sulfur battery electrolyte, C 18 H 15 The molar concentration of Bi is 0.1 mol / L.
[0081] Example 9
[0082] This embodiment provides a lithium-sulfur battery electrolyte, which differs from Embodiment 7 only in that:
[0083] The bismuth-containing organic additive is C 21 H 21 Bi (tri-o-tolyl bismuth), based on the total volume of the lithium-sulfur battery electrolyte, has a molar concentration of 0.005 mol / L.
[0084] Example 10
[0085] This embodiment provides a lithium-sulfur battery electrolyte, which differs from Embodiment 7 only in that:
[0086] The bismuth-containing organic additive is C 21 H 21 Bi (tri-o-tolyl bismuth), based on the total volume of the lithium-sulfur battery electrolyte, has a molar concentration of 0.01 mol / L.
[0087] Embodiment 11
[0088] This embodiment provides a lithium-sulfur battery electrolyte, which differs from Embodiment 7 only in that:
[0089] The bismuth-containing organic additive is C 21 H 21 Bi (tri-o-tolyl bismuth), based on the total volume of the lithium-sulfur battery electrolyte, has a molar concentration of 0.1 mol / L.
[0090] Comparative Example 2
[0091] This comparative example provides a lithium-sulfur battery electrolyte, which differs from Example 7 only in that:
[0092] Contains no bismuth-containing organic additives.
[0093] Lithium-sulfur battery examples and comparative examples
[0094] Example I
[0095] This embodiment provides a series of lithium-sulfur batteries, which are manufactured by a manufacturing method comprising the following specific steps:
[0096] Preparation of positive electrode materials:
[0097] A carbon-sulfur composite material (sulfur content 65wt%), carbon black (Super P) and polyacrylic acid (PAA) are mixed in a mass ratio of 8:1:1, and an appropriate amount of high-purity water is added to the mixture, and then the mixture is ball-milled in a ball mill, wherein the speed of the ball mill is 500 rpm and the ball-milling time is 6h; the slurry obtained after ball milling is evenly spread on a carbon-coated aluminum foil, and then vacuum-dried at 60°C for 12h, and the carbon-coated aluminum foil after vacuum drying is used as a positive electrode material.
[0098] Production of lithium-sulfur batteries:
[0099] Using metallic lithium sheet as the negative electrode material, PP / PE / PP three-layer composite film as the battery separator, the lithium-sulfur battery electrolytes provided in Examples 1 to 6 and Comparative Example 1 were respectively the electrolytes, and a series of button batteries were assembled in an argon environment glove box (H2O<0.1ppm, O2<0.1ppm).
[0100] Example II
[0101] This embodiment provides a series of lithium-sulfur batteries, which are manufactured by a manufacturing method comprising the following specific steps:
[0102] Preparation of positive electrode materials:
[0103] A carbon-sulfur composite material (sulfur content 65wt%), carbon black (Super P) and polyacrylic acid (PAA) are mixed in a mass ratio of 8:1:1, and an appropriate amount of high-purity water is added to the mixture, and then the mixture is ball-milled in a ball mill, wherein the speed of the ball mill is 500 rpm and the ball-milling time is 8h; the slurry obtained after ball milling is evenly spread on a carbon-coated aluminum foil, and then vacuum-dried at 60°C for 24h, and the carbon-coated aluminum foil after vacuum drying is used as a positive electrode material.
[0104] Production of lithium-sulfur batteries:
[0105] Using metallic lithium sheet as the negative electrode material, PP / PE / PP three-layer composite film as the battery separator, the lithium-sulfur battery electrolytes provided in Examples 7 to 11 and Comparative Example 2 were respectively the electrolytes, and a series of button batteries were assembled in an argon environment glove box (H2O<0.1ppm, O2<0.1ppm).
[0106] Test Example 1
[0107] In this test example, a series of button cells provided in Example I are tested for battery cycle performance on a charge and discharge instrument. Specifically, the batteries are tested for charge and discharge cycles at charge and discharge rates of 0.2 / 0.2C and 0.5 / 0.5C, respectively, with a cut-off voltage range of 1.6-2.6V.
[0108] The experimental data obtained in this test case are shown in Table 1 and Figure 1 shown.
[0109] Table 1 Test results of a series of button cells provided in Example Ⅰ at 0.5C rate
[0110]
[0111] From the results of Examples 1 to 6 and Comparative Example 1 shown in Table 1 above, it can be seen that the lithium-sulfur battery assembled with the lithium-sulfur battery electrolyte provided in Comparative Example 1 as the electrolyte has a first-cycle discharge specific capacity of only 708.5 mAh / g at a discharge rate of 0.5 C, which is 205.1-229.9 mAh / g lower than the first-cycle discharge specific capacity of the lithium-sulfur battery assembled with the lithium-sulfur battery electrolyte provided in Examples 1 to 6 as the electrolyte. From the perspective of cycle performance, the capacity retention rate of the lithium-sulfur battery assembled with the lithium-sulfur battery electrolyte provided in Comparative Example 1 as the electrolyte after 100 cycles is only 61.5%, which is 27.0-32.1% lower than the capacity retention rate of the lithium-sulfur battery assembled with the lithium-sulfur battery electrolyte provided in Examples 1 to 6 as the electrolyte. In addition, it can be seen from Table 1 that the coulombic efficiency of the lithium-sulfur battery assembled using the lithium-sulfur battery electrolyte provided in Examples 1 to 6 as the electrolyte is also significantly higher than that of the lithium-sulfur battery assembled using the lithium-sulfur battery electrolyte provided in Comparative Example 1 as the electrolyte.
[0112] from Figure 1It can be seen that at a discharge rate of 0.2C, the initial discharge specific capacity of the lithium-sulfur battery assembled using the lithium-sulfur battery electrolyte provided in Comparative Example 1 as the electrolyte is 1163.7 mAh / g, while the initial discharge specific capacity of the lithium-sulfur battery assembled using the lithium-sulfur battery electrolyte provided in Example 1 of the present invention as the electrolyte is 1218.9 mAh / g, which is 55.2 mAh / g higher than that of Comparative Example 1, indicating that the bismuth-containing organic additive is beneficial to improving the discharge specific capacity of the lithium-sulfur battery. At a discharge rate of 0.5C, the initial discharge specific capacity of the lithium-sulfur battery assembled using the lithium-sulfur battery electrolyte provided in Comparative Example 1 as the electrolyte is 608.5 mAh / g, the discharge specific capacity after 100 cycles is 335.8 mAh / g, and the capacity retention rate is only 55.2%; while the initial discharge specific capacity of the lithium-sulfur battery assembled using the lithium-sulfur battery electrolyte provided in Example 1 as the electrolyte is 882.4 mAh / g at a discharge rate of 0.5C, which is 273.9 mAh / g higher than that of Comparative Example 1, and the discharge specific capacity after 100 cycles is 822.7 mAh / g, and the capacity retention rate is as high as 93.2%, which is 38.0% higher than that of Comparative Example 1.
[0113] It can be seen that bismuth-containing organic additives in lithium-sulfur battery electrolytes can significantly improve the rate performance and cycle performance of lithium-sulfur batteries.
[0114] Test Example 2
[0115] In this test example, a series of button batteries provided in Example II are tested for battery cycle performance on a charge and discharge instrument. Specifically, the batteries are tested for charge and discharge cycles at a charge and discharge rate of 0.5 / 0.5C, and the cut-off voltage range is 1.5-2.8V.
[0116] The experimental data obtained in this test example are shown in Table 2 below.
[0117] Table 2 Test results of a series of button cells provided in Example II at 0.5C rate
[0118]
[0119]
[0120] As shown in Table 2 above, the results of Examples 7 to 11 and Comparative Example 2 show that the lithium-sulfur battery assembled with the lithium-sulfur battery electrolyte provided in Comparative Example 2 as the electrolyte has a first-cycle discharge specific capacity of only 865.3 mAh / g at a discharge rate of 0.5 C, which is 143.4-240.9 mAh / g lower than the first-cycle discharge specific capacity of the lithium-sulfur battery assembled with the lithium-sulfur battery electrolyte provided in Examples 7 to 11 as the electrolyte. From the perspective of cycle performance, the capacity retention rate of the lithium-sulfur battery assembled with the lithium-sulfur battery electrolyte provided in Comparative Example 1 as the electrolyte after 100 cycles is only 56.2%, which is 33.1-36.8% lower than the capacity retention rate of the lithium-sulfur battery assembled with the lithium-sulfur battery electrolyte provided in Examples 7 to 11 as the electrolyte. In addition, it can be seen from Table 2 that the coulombic efficiency of the lithium-sulfur battery assembled using the lithium-sulfur battery electrolyte provided in Examples 7 to 11 as the electrolyte is also significantly higher than that of the lithium-sulfur battery assembled using the lithium-sulfur battery electrolyte provided in Comparative Example 2 as the electrolyte.
[0121] It can be seen that bismuth-containing organic additives in lithium-sulfur battery electrolytes can significantly and effectively improve the rate performance and cycle performance of lithium-sulfur batteries.
[0122] In summary, by comparing the test results of the embodiment of the present invention with those of the comparative example, it can be seen that compared with the existing conventional lithium-sulfur battery electrolyte, the lithium-sulfur battery electrolyte containing bismuth-containing organic additive provided by the embodiment of the present invention exhibits more excellent electrochemical performance. This is because the bismuth-containing functional groups in the bismuth-containing organic additives are easy to form complexes with polysulfides (lithium polysulfide) in the electrolyte, promoting the redox reaction between long-chain polysulfides and short-chain sulfides. The formed bismuth-sulfur bonds can effectively prevent the loss of polysulfides and improve the discharge specific capacity and capacity retention rate of lithium-sulfur batteries; the bismuth-containing functional groups in the bismuth-containing organic additives can also serve as catalysts to accelerate the conversion rate of polysulfides and improve the discharge rate performance of the battery; in addition, during the charging process, the bismuth-containing organic additives can also be decomposed in situ, and the bismuth-containing functional groups are easy to alloy with the lithium metal negative electrode on the surface of the lithium metal negative electrode to form a bismuth-lithium alloy phase structure, thereby forming a uniform lithium deposition site, which can reduce the deposition surface energy of lithium, effectively slow down the nucleation and growth probability of lithium dendrites, improve the capacity retention rate and cycle stability of the battery, and improve the cycle life and safety of the lithium-sulfur battery.
[0123] The above is only a specific embodiment of the present invention, and cannot be used to limit the scope of the invention. Therefore, the replacement of equivalent components, or equivalent changes and modifications made according to the protection scope of the patent of the present invention, should still fall within the scope of this patent. In addition, the technical features of the present invention can be freely combined with each other, with each other and with each other, and with each other.
Claims
1. A lithium-sulfur battery electrolyte, characterized in that: Based on the total volume of the lithium-sulfur battery electrolyte, it contains a lithium salt with a molar concentration of 0.2-2 mol / L, a bismuth-containing organic additive with a molar concentration of 0.005-0.2 mol / L, and a balance of an organic solvent.
2. The lithium-sulfur battery electrolyte according to claim 1, characterized in that: The bismuth-containing organic additive includes at least one of triphenylbismuth, bismuth trifluoromethanesulfonate, tri-p-tolylbismuth and tri-o-tolylbismuth.
3. The lithium-sulfur battery electrolyte according to claim 1 or 2, characterized in that: The lithium salt includes at least one of lithium bis(trifluoromethanesulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium perchlorate, lithium hexafluorophosphate and lithium nitrate.
4. The lithium-sulfur battery electrolyte according to claim 1 or 2, characterized in that: The organic solvent includes at least two of 1,3-dioxolane, ethylene glycol dimethyl ether, ethylene carbonate, fluorinated ethylene carbonate, dimethyl carbonate, diethyl carbonate, dimethyl trisulfide, and dimethyl disulfide.
5. The method for preparing a lithium-sulfur battery electrolyte according to any one of claims 1 to 4, characterized in that: The preparation method comprises: Step 1: In a glove box filled with inert gas, mix the required organic solvents according to the proportion, and mix them evenly to obtain a basic solution; Step 2: Add the dried lithium salt to the basic solution and mix well to obtain a basic electrolyte; Step 3: Add the bismuth-containing organic additive to the basic electrolyte and mix well to obtain a lithium-sulfur battery electrolyte.
6. The preparation method according to claim 5, characterized in that: In step 1, the inert gas includes argon.
7. The preparation method according to claim 5 or 6, characterized in that: In step 1, the water and oxygen contents in the glove box are both less than 0.1 ppm.
8. The preparation method according to claim 5 or 6, characterized in that: In step 2, the drying is performed at 100-150° C. for 12-24 hours.
9. Use of the lithium-sulfur battery electrolyte according to any one of claims 1 to 4 as an electrolyte for lithium-sulfur batteries.
10. A lithium-sulfur battery, characterized in that: The electrolyte used in the lithium-sulfur battery is the lithium-sulfur battery electrolyte according to any one of claims 1 to 4.